á,(x+7)2-y2
= (x+7+y)(x+7-y)
b, (x+1)(x-25)
chúc bạn luôn thành công trong cuộc sống nha
a)
\(x^2-y^2+14x+49\)
\(=\left(x^2+14x+49\right)-y^2\)
\(=\left(x^2+2.7.x+7^2\right)-y^2\)
\(=\left(x+7\right)^2-y^2\)
\(=\left(x+y+7\right)\left(x-y+7\right)\)
Vậy ...
b)
\(x^2-24x-25\)
\(=x^2-24x+144-169\)
\(=\left(x^2-24x+144\right)-169\)
\(=\left(x^2-2.12.x+12^2\right)-13^2\)
\(=\left(x-12\right)^2-13^2\)
\(=\left(x-12+13\right)\left(x-12-13\right)\)
\(=\left(x+1\right)\left(x-25\right)\)
Vậy ...
Ngoài ra câu b mình còn có một cách khác :
\(x^2-24x-25\)
\(=x^2-25x+x-25\)
\(=\left(x^2-25x\right)+\left(x-25\right)\)
\(=\left(x-25\right)x+\left(x-25\right)\)
\(=\left(x+1\right)\left(x-25\right)\)